2020
DOI: 10.3390/v12121460
|View full text |Cite
|
Sign up to set email alerts
|

Integrase-Defective Lentiviral Vectors for Delivery of Monoclonal Antibodies against Influenza

Abstract: Delivering rapid protection against infectious agents to non-immune populations is a formidable public health challenge. Although passive immunotherapy is a fast and effective method of protection, large-scale production and administration of monoclonal antibodies (mAbs) is expensive and unpractical. Viral vector-mediated delivery of mAbs offers an attractive alternative to their direct injection. Integrase-defective lentiviral vectors (IDLV) are advantageous for this purpose due to the absence of pre-existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In a pre-clinical study, a single immunisation of NILVs encoded in a secreted form of the envelope of a virulent strain of West Nile virus (WNV) induced a strong B cell response, and a single immunisation was also sufficient to induce early and long-lasting protective immunity [ 78 , 79 ]. On the other hand, one in vivo study involving the H5 influenza A virus (IAV) demonstrated that the monoclonal antibody (mAb) administered through NILVs did not persist for longer time points [ 80 ]. However, this could be studied further to make it an effective strategy for rapid protection against infectious diseases in the future.…”
Section: Clinical Application Of Nilvsmentioning
confidence: 99%
“…In a pre-clinical study, a single immunisation of NILVs encoded in a secreted form of the envelope of a virulent strain of West Nile virus (WNV) induced a strong B cell response, and a single immunisation was also sufficient to induce early and long-lasting protective immunity [ 78 , 79 ]. On the other hand, one in vivo study involving the H5 influenza A virus (IAV) demonstrated that the monoclonal antibody (mAb) administered through NILVs did not persist for longer time points [ 80 ]. However, this could be studied further to make it an effective strategy for rapid protection against infectious diseases in the future.…”
Section: Clinical Application Of Nilvsmentioning
confidence: 99%
“…Apart from pseudotyping, the expression of antibodies transgene carried by IDLV also elicits immune responses towards the targeted pathogens. Michelini et al (2020) vaccinated mice with engineered IDLV carrying genes encoding for VN04-2 monoclonal antibodies (mAbs) against influenza A virus (IAV). Expression of VN04-2 mAbs in the vaccinated mice provides some protection against H3N2 IAV, even though the mAbs are specific H5 HA.…”
Section: Applications Of Idlv For Clinical Implementationsmentioning
confidence: 99%
“… 7 , 8 Nasal delivery of viral vectors encoding anti-influenza IgG has also been tested successfully in mice. 9 More limited experiences have been reported for monkeypox virus 10 and respiratory syncytial virus. 11 Again, no clinical study has been run for those pathogens.…”
Section: Introductionmentioning
confidence: 99%